TEACHRER COACHING IN NIGERIA; A STRATEGY FOR ENHANCING TEACHERS’ INSTRUCTIONAL SKILLS AND STUDENTS' LANGUAGE SKILLS - Muhammad Mukhtar Aliyu (State Islamic University of North Sumatra Indonesia, 2019)
In Nigeria, students’ poor language skills have been documented at the three levels (primary, secondary and tertiary) of education. One of the factors contributing to the problem is the poor teaching methods adopted by many teachers in their classrooms. Many teachers have little or no professional training. They are unaware of new approaches that have been proven effective in developing students’ language skills and learning outcome in general. Studies have shown that teacher coaching improves teachers’ instructional performance which in turn enhances students’ learning outcomes in many countries. However, there is a lack of teacher coaching program in Nigeria. Therefore, this paper reviews some previous studies which revealed the importance and effectiveness of teacher coaching in improving students’ learning output. It reviews some essential factors to be considered while designing effective teacher-coaching programs such as knowledge and skills for teacher coaching, responsibility for coaches, and coaching process, evaluation and other supports. The paper makes some recommendations on how to implement teacher coaching, particularly in Northern Nigeria in order to improve the students’ learning output. Finally, the paper has contributed in outlining essential requirements in designing effective teacher coaching strategies which include professional development of coaches, time allocated to teacher/coach interactions, establishment and maintenance of collaborative relationships between coaches and teachers, the constructive feedback and tools used during and between coaching sessions, the ratio of teachers to coaches (10:1) in urban and (5:1) rural areas, and regular visits that teachers receive from their coaches on a weekly and monthly basis.